APPLYING OF MS EXCEL 2010 FOR 2D COLOUR VISUALIZATION OF TEMPERATURE FIELDS IN LOGS DURING THEIR DEFROSTING PART 1. SEQUENCE OF PROCEDURES FOR THE CREATION OF 2D COLOUR DIAGRAMS USING MS EXCEL 2010 (Innovation in Woodworking Industry and Engineering design, 2026)
A methodology for the creation of colourful 2D diagrams using MS Excel 2010, illustrating the temperature distributions in the longitudinal sections of frozen logs during different moments of their defrosting, has been suggested in this paper. For the creation of the diagrams numerical results have been used, which represent the solutions to a non-linear mathematical model of the logs’ defrosting process. These numerical results are presented in files in the .txt format before their processing with the software of MS Excel 2010 aiming at the creation of the 2D colourful diagrams.